Persistent oxidative stress in vestibular schwannomas after stereotactic radiation therapy - Robinett, Zachary N. (Otol Neurotol, 2018)
OBJECTIVE: Stereotactic radiation therapy is increasingly used to treat vestibular schwannomas (VSs) primarily and to treat tumor remnants following microsurgery. Little data are available regarding the effects of radiation on VS cells. Tyrosine nitrosylation is a marker of oxidative stress following radiation in malignant tumors. It is not known how long irradiated tissue remain under oxidative stress, and if such modifications occur in benign neoplasms such as VSs treated with significantly lower doses of radiation. We immunostained sections from previously radiated VSs with an antibody that recognizes nitrosylated tyrosine residues to assess for ongoing oxidative stress. STUDY DESIGN: Immunohistochemical analysis. METHODS: Four VSs, which recurred after excision, were treated with stereotactic radiation therapy. Ultimately each tumor required salvage re-resection for regrowth. Histologic sections of each tumor before and after radiation were immunolabeled with a monoclonal antibody specific to nitrotyrosine and compared. Two VSs that underwent re-resection of a growing tumor remnant without prior radiation therapy served as additional controls. RESULTS: Irradiated tumors enlarged in volume by 3.16-8.62 mL following radiation. Pre-radiation sections demonstrated little to no nitrotyrosine immunostaining. Three of four of irradiated VSs demonstrated increased nitrotyrosine immunostaining in the post-radiation sections compared to pre-radiation tumor sections. Non-irradiated VSs did not label with the anti-nitrotyrosine antibody. CONCLUSIONS: VSs exhibit oxidative stress up to seven years after radiotherapy, yet these VSs continued to enlarge. Thus, VSs that grow following radiation appear to possess mechanisms for cell survival and proliferation despite radiation induced oxidative stress.